The Effect of Using P3M Media on Understanding the Concept of Multiplication and Division of Fifth Grade Students - Lailatul Magfiroh; Uki Suhendar; Dwi Avita (Universitas Pendidikan Ganesha, 2023)
Instilling concept of multiplication and division to students is influenced by learning media. But currently there are still many teachers who do not use good learning media. The research conducted aims to analyze how much influence P3M media has on students' understanding of the concept of multiplication and division. The method used in this study is a Quasi-Experimental method with the type used is Post-test Only Control Group Design. The sample in this study was 15 students as the control class and 15 students as the experimental class from fifth grade students. Because the data did not meet the normality test, the Mann-Whitney test was used and the results obtained were a significance value of 0.001 <0.05 or Ha was accepted. It can be said that there are differences in the application of P3M media to the concept of multiplication and division in the control class and the experimental class. So it is said that there is an effect of using P3M media on understanding the concept of multiplication and division of students. Nothing but learning using P3M learning media in understanding the concept of multiplication and division in students becomes more effective than learning without the application of media.